Study of anti-fibrillogenic activity of iron(II) clathrochelates - Kovalska, Vladyslava B.; Losytskyy, Mykhaylo Yu.; Varzatskii, Oleg A.; Cherepanov, Vsevolod V.; Voloshin, Yan Z.; Mokhir, Andriy; Yarmoluk, Sergiy M.; Volkov, Sergiy V. (Bioorganic & medicinal chemistry, 2014)
The macrocyclic compounds mono- and bis-iron(II) clathrochelates were firstly studied as potential anti-fibrillogenic agents using fluorescent inhibitory assay, atomic force microscopy and flow cytometry. It is shown that presence of the clathrochelates leads to the change in kinetics of insulin fibrillization reaction and reduces the amount of formed fibrils (up to 70%). The nature of ribbed substituent could determine the activity of clathrochelates - the higher inhibitory effect is observed for compounds containing carboxybenzenesulfide groups, while the inhibitory properties only slightly depend on the size of complex species. The mono- and bis-clathrochelate derivatives of meta-mercaptobenzoic acid have close values of IC namely 16 ± 2 and 24 ± 5 μM, respectively. The presence of clathrochelates decreases the fibril diameter from 5-12 nm for free insulin fibrils to 3-8 nm for these formed in the clathrochelate presence, it also prevents the lateral aggregation of mature fibrils and formation of superfibrillar clusters. However the addition of clathrochelate results in more heterogeneous (both by size and structure) insulin aggregates population as compared to the free insulin. This way, cage complexes - iron(II) clathrochelates are proposed as efficient agents able to suppress the protein aggregation processes. © 2014 Elsevier Ltd. All rights reserved.